Exercise Mediated Nrf2 Signaling Protects the Myocardium From Isoproterenol-Induced Pathological Remodeling - Shanmugam, Gobinath; Challa, Anil K.; Devarajan, Asokan; Athmanathan, Baskaran; Litovsky, Silvio H.; Krishnamurthy, Prasanna; Davidson, Christopher J.; Rajasekaran, Namakkal Soorappan (Frontiers in Cardiovascular Medicine, 2019)
Although exercise derived activation of Nrf2 signaling augments myocardial antioxidant signaling, the molecular mechanisms underlying the benefits of moderate exercise training (MET) in the heart remain elusive. Here we hypothesized that exercise training stabilizes Nrf2-dependent antioxidant signaling, which then protects the myocardium from isoproterenol-induced damage. The present study assessed the effects of 6 weeks of MET on the Nrf2/antioxidant function, glutathione redox state, and injury in the myocardium of C57/BL6J mice that received isoproterenol (ISO; 50 mg/kg/day for 7 days). ISO administration significantly reduced the Nrf2 promoter activity (p < 0.05) and downregulated the expression of cardiac antioxidant genes (Gclc, Nqo1, Cat, Gsr, and Gst-μ) in the untrained (UNT) mice. Furthermore, increased oxidative stress with severe myocardial injury was evident in UNT+ISO when compared to UNT mice receiving PBS under basal condition. Of note, MET stabilized the Nrf2-promoter activity and upheld the expression of Nrf2-dependent antioxidant genes in animals receiving ISO, and attenuated the oxidative stress-induced myocardial damage. Echocardiography analysis revealed impaired diastolic ventricular function in UNT+ISO mice, but this was partially normalized in the MET animals. Interestingly, while there was a marginal reduction in ubiquitinated proteins in MET mice that received ISO, the pathological signs were attenuated along with near normal cardiac function in response to exercise training. Thus, moderate intensity exercise training conferred protection against ISO-induced myocardial injury by augmentation of Nrf2-antioxidant signaling and attenuation of isoproterenol-induced oxidative stress.